A Framework for Deliberation and Negotiation among BDI Agents - Rueda, Sonia Vivian (2005)
This work presents an interaction model among collaborative agents based on dialogues. For the specification we use a formalism, called Dialogue Games, which allows to describe the nature of the utterances available in each dialogue. We propose an interaction language which favors deliberation and argumentationbased negotiation among BDI agents. For each locution's specification we establish a set of preconditions, its meaning, the expected responses, and the modifications that it could produce. The interaction protocol and the interaction language as a whole can be used for specifying meaningful interaction between dialogical partners by following the rules of an individual dialogue.